Peran Perpustakaan Sekolah sebagai Sarana Pengembangan Budaya Literasi pada Siswa SMAN 2 Kota Cirebon - Kusumawardhani, Yasmine (Pustabiblia: Journal of Library and Information Science, 2023)
With the rapid changes in technology, the world’s needs for generational growth are getting increasingly intense. A superior generation necessitates a competent level of education accompanied by improved literacy skills. Schools, as educational institutions, should encourage their pupils to develop a literacy culture. The school library, as an information shelter institution in schools, should also contribute to the development of a literacy culture by providing multiple access points that children may easily ac- cess. As a result, this study was conducted to determine the role of the school library at SMAN 2 Cirebon in the development of a literacy culture among students. The research method used in the study is a descriptive qualitative method combining an interview and direct observation research method. The information obtained will be supported by research in the form of library research, which will use relevant library data to identify and describe in detail service activities at SMAN 2 Cirebon’s school library and the literacy program that has been implemented. According to the results of this study, the school library at SMAN 2 Cirebon has contributed in the development of a literacy culture among students. The literacy program that has been implemented in the school environment had a positive impact on students and encouraged them to read. The literacy program implemented by the school is deemed to be more effective because of the availability of quality services supplied by the school library. However, it is very unfortunate that the library has not digitized the library.